Diversity of Land Arthropods in Community Oil Palm Plantations in the Coastal Area of Bengkulu - Fauzi, Ariffatchur; Zarkani, Agustin; Djamilah, Djamilah; Gustian, Deri; Hamidi, Ilmi; Ifebri, Rihan; Prastio, Turko (Badan Penerbitan Fakultas Pertanian (BPFP), 2025)
Bengkulu is one of the provinces located on the island of Sumatra, boasting a significant agricultural sector. One of the leading agrarian commodities in Bengkulu Province is oil palm. Oil palm in Bengkulu is planted in coastal areas. One of the key factors supporting oil palm fruit production is a healthy soil arthropod ecosystem. Soil arthropods play an essential role in the oil palm plantation ecosystem. As organisms that live in the soil, these animals help maintain soil and plant health, improving soil structure and nutrient availability for oil palm plants. This study aims to obtain initial data on the diversity of soil arthropods and their roles in smallholder oil palm plantations on the coast of Bengkulu. This study began with sampling oil palm plantations around the coast of Bengkulu. The areas that will be used as study locations include Sungai Suci, Danau Gedang, and Pekik Nyaring. Arthropod sampling was carried out by installing pitfall traps in both areas, which were determined diagonally in a ​​200 m² area, with 20 pitfall trap units per location. Arthropod species were identified based on morphology, and the type and number of populations were recorded. The Shannon-Wiener diversity index, dominance index, and evenness index measure analysis of biodiversity data. The results of the study showed that in the majority, the diversity of soil arthropods in the three sampling areas was moderate, the dominance of arthropod types was low to moderate, and evenness was moderate to high.